PERFECTION OF CONSTRUCTION OF THE COOLING DEVICES OF THE COOLING LINES OF THE BAR REINFORCING ROLLED PRODUCTS OF RUP "BMZ" - S. M. Zhuchkov; V. A. Matochkin; D. N. Andrianov; M. A. Murikov; N. I. Anelkin; A. V. Rusalenko; P. V. Tokmakov; A. I. Leshchenko (Литьë и металлургия)
The peculiarities of construction of thermomechanical hardening of rolled metal of operating line of the m ill 3 20 cooling are considered, their merits and demerits are analyzed.